Application of Inquiry Based Learning Model Assisted by Media Pictures to Improve Student Learning Outcomes at SMP Negeri 5 Waibakul - Margaretha R Sedu Dairu; Vidriana Oktoviana Bano (Formosa Journal of Multidisciplinary Research, 2023)
This study aims to improve student learning outcomes through the application of the Inquiry Based Learning (IBL) learning model. The type of research is PTK, the Kemmis and Mc models. Taggart with a quantitative descriptive approach. The research consisted of pre-cycle activities, cycle I and cycle II. The research subjects were 23 class VIII students of SMP Negeri 5 Waibakul, academic year 2022/2023. Pre-cycle, students who complete 17.39%, who do not complete 82.60%. Cycle I, which was completed with a percentage of 43.47% and which was incomplete with a percentage of 56.52% with an average value of 63.91. then on the affective aspect there are 2 very good predicates with a percentage of 8.7%, 3 good predicates with a 13% percentage, 12 moderately good predicates with a percentage of 52.2%, 6 poor predicates with a percentage of 26.1%. Cycle II, consisting of 21 people completed with a percentage of 91.30% and 2 people did not complete with a percentage of 8.69% with an average value of 76.56, while the value of the affective aspect of the predicate was very good 5 people with a percentage of 21.7%, 16 people with a good rating with a percentage of 69.6%, 2 people with a fairly good rating with a percentage of 8.7%. The application of the Inquiry Based Learning learning model assisted by media images can improve learning outcomes in class VIII of SMP Negeri 5 Waibakul.